Intentional Forgetting of Emotional Words after Trauma: A Study with Victims of Sexual Assault - Blix, Ines; Brennen, Tim (Frontiers in Psychology, 2011)
Following exposure to a trauma, people tend to experience intrusive thoughts and memories about the event. In order to investigate whether intrusive memories in the aftermath of trauma might be accounted for by an impaired ability to intentionally forget disturbing material, the present study used a modified Directed Forgetting (DF) task to examine intentional forgetting and intrusive recall of words in sexual assault victims and controls. By including words related to the trauma in addition to neutral, positive and threat-related stimuli it was possible to test for trauma-specific effects. No difference between the Trauma and the Control group was found for correct recall of to-be-forgotten (F) words or to-be-remembered (R) words. However, when recalling words from R- list, the Trauma group mistakenly recalled significantly more trauma-specific words from F- list. “Intrusive“ recall of F trauma words when asked to recall R-words was related to symptoms of intrusion reported on the IES.